Navigating the Higher Education landscape: What hope do Enabling students have? (Journal of University Teaching and Learning Practice, 2026)
Navigating the landscape of Higher Education can be particularly challenging for Enabling students, with their ability to persevere and maintain feelings of ‘hope’ likely to impact their confidence to complete their Enabling program. This paper explores the impact of hope on student perseverance and progress within an Enabling program. Using data collected from in-depth interviews with two participants, we investigate how hope shapes students’ motivation, resilience, and ultimately their ability to cope with academic challenges. The findings reveal that hope serves as a critical psychological resource, fostering a sense of agency and goal-directed behaviour that can enable students to flourish in their educational journeys. Through interpreting participants’ experiences using the lens of hope theory (Snyder, 2000) educators in the Enabling space can better appreciate how students navigated obstacles and sustained their commitment to the program. This paper contributes to the understanding of hope as a vital resource in educational contexts, situated within the growing discourse on equity, access, and the emotional dimensions of learning in transitional educational contexts.